Modeling the mechanism of generation of vesicular breath sounds - Vovk, I. V.; Matsypura, V. T. (Reports of the National Academy of Sciences of Ukraine, 2015)
We present a mathematical model of the process of generation of vesicular breath sounds based on the assumption of a significant contribution of the vibration of alveoli walls to the sound formation during breathing. We develop a model of alveolus wall in the form of a membrane and show that, with its periodic extension, transverse vibrations resulting in the sound generation can occur. We determine characteristics of the composite noise signal formed during the simultaneous excitation of membranes with different mechanical characteristics. Based on the analysis of such a signal, we found that its shape and fractal properties are close enough to those of the real vesicular breath sounds.